Desain UI/UX Rakabu Furniture Sebagai Media Promosi - Hafiz Sa'id Billah, Ahnaf; Henny Lukitasari, Evelyne; Khoirul Anwar, Ahmad (JURNAL ASSOSIATIV, 2024)
Indonesia has large potential forestry resources. This potential creates higher competition in the furniture industry. One of the local furniture companies is Rakabu Furniture. This company produces furniture and processes wood, which has entered the international market. Besides, Rakabu Furniture only promotes products through exhibitions, so it has not been able to expand its market. The solution to this problem is creating a User Interface (UI) / User Experience (UX) design on the web as an effort to expand the market and design an ordering system that is easier and more efficient. Rakabu Furniture's UI/UX design emphasizes the company's image to produce an attractive design that is in line with the company's vision and mission. The design method used qualitative methods by collecting data and interviewing the informant from Rakabu Furniture. The results show that a UI/UX website design aims to understand the message from Rakabu Furniture as a promotional medium for new companies and is supported by several other media.Keywords: Design, User Interface (UI), User Experience (UX), Rakabu Furniture, PromotionalMedia.